Unemployment, the Great Recession, and apprenticeship attrition in the U.S. (3rd April 2018) - Bilginsoy, Cihan
Abstract: The author estimates the impacts of the local rate of unemployment and the Great Recession on the quit and graduation rates of the U.S. construction trade apprentices over the 2001–2014 period. Trade union participation in training sponsorship had a strong influence on attrition rates. The impacts of the business cycle and the Great Recession on the attrition rate also varied across sponsor types. During downturns, apprenticeship duration of the quitters in union-employer jointly sponsored programmes was longer, suggesting that the trainees were able to stay with the programme as jobs become scarcer. However, during the Great Recession the quit hazard among these trainees increased, which indicates declining long-term career prospects. In contrast, apprentices in unilateral multiple-employer programmes dropped out at faster rates during the downturns,  except during the Great Recession. The increase in the staying power of the quitters in employer-only programmes during the Great Recession is a puzzle. The eventual probability of cancellation was lower among the union-employer  joint programmes than in the employer-only programmes, although the difference narrowed down during the Great Recession.